Horticulture applicability of 3D laser scanner - Riczu, Péter; Tamás, János; Nagy, Gábor; Nagy, Attila; Fórián, Tünde; Jancsó, Tamás (Acta Agraria Debreceniensis, 2012)
As a result of the technological development, remote sensing instruments and methods have become widespread in all segments of life (from precision agriculture through architecture to medicine). Among the innovative development of remote sensing instruments the 3D laser scanner is overriding importance. The horticulture applicability of terrestrial laser scanning technique is innovation in the precision agriculture, because it could be determine the structure of trees and branches, the canopy extension, which can help to recognize some biophysical parameters. The examination was carried out with Leica ScanStation C10 terrestrial laser scanner in the Study and Regional Research Farm of the University of Debrecen near Pallag. In this article I present the measuring principle, the parameters and horticulture applicability of the terrestrial laser scanner.